ANALISIS KEBUGARAN JASMANI PADA PEGIAT INORGA FOKBI JAMBI - Aritonang, Luccy Hanna; Sukendro; Fitri Khairunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the level of physical fitness among participants of INORGA FOKBI Jambi, with a particular focus on the cardiorespiratory endurance component. The research employed a quantitative descriptive method using a purposive sampling technique. The sample consisted of 10 active FOKBI Jambi participants, comprising 4 males and 6 females. The instrument used in this study was the Bleep Test (Multistage Fitness Test) to measure VO₂Max capacity as an indicator of cardiorespiratory endurance. Data were analyzed using descriptive statistical techniques in the form of percentages.The results indicated that the overall physical fitness level of INORGA FOKBI Jambi participants was categorized as good and moderate. A total of 6 participants (60%) were classified in the good category, while 4 participants (40%) were classified in the moderate category. Among male participants, the majority were categorized as good, accounting for 75% of the sample. Meanwhile, female participants were equally distributed between the good and moderate categories. The highest VO₂Max value recorded was 44.9 ml/kg/min, while the lowest was 30.2 ml/kg/min. No participants were classified in the poor or very poor categories. Based on the findings, it can be concluded that the physical fitness level of INORGA FOKBI Jambi participants is relatively good and sufficient to support physical activities involved in aerobic exercise programs. Nevertheless, structured and continuous aerobic training is still necessary to further improve cardiorespiratory endurance and achieve a more optimal level of physical fitness.